2017
DOI: 10.1590/1806-9061-2016-0334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gaba on the Thymus Cytokines of Wenchang Chickens Submitted to Heat Stress

Abstract: Under routine feeding conditions, 1-day-old male chicks were randomly divided into control group (CK), heat-stress group (HS), and GABA + heat stress group (GABA+HS). The thymus contents of IL-1, IL-2, TGF-β1, IFN-γ, GH and HSP70 were determined by enzyme-linked immunosorbent assays. The results showed that: (1) IL-1 and TGF-β1 contents of HS group were significantly lower than those of the CK group (p<0.05), and those of the GABA+HS group were significantly higher relative to the HS group (p<0.05); (2) IL-2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, IFN-γ plasma levels were significantly lower in the TM group at 0 h, compared to the controls, and AHS increased plasma IFN-γ levels only in TM chicks. Correspondingly, previous studies have reported increased IFN-γ expression in chickens during heat stress conditions [14,41]. In contrast, another study has showed that heat-stressed broiler chickens possessed lower levels of IFN-γ expression [5].…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, IFN-γ plasma levels were significantly lower in the TM group at 0 h, compared to the controls, and AHS increased plasma IFN-γ levels only in TM chicks. Correspondingly, previous studies have reported increased IFN-γ expression in chickens during heat stress conditions [14,41]. In contrast, another study has showed that heat-stressed broiler chickens possessed lower levels of IFN-γ expression [5].…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have found that oxidative stress can cause damage to the antioxidant enzyme system of human chorionic trophoblast cells [ 26 ]. Research on GABA in livestock and poultry production mainly focuses on resisting heat stress and regulating appetite [ 27 , 28 , 29 ], but the effects of GABA on alleviating the oxidative stress of embryonic trophoblast cells are still unknown. Our results found that oxidative stress induced by H 2 O 2 reduced the activity of SOD, CAT, and GSH-Px, while the 100 and 200 μmol/L GABA pretreatments can significantly increase the activity of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In laying hens, supplementation with GABA has been found to positively affect egg quality in terms of improved laying hen quality [6]. It was also found that GABA increases the immune responses in chickens during stress conditions [7]. Therefore, GABA is a valuable metabolite that can be applied to humans and livestock.…”
Section: Introductionmentioning
confidence: 99%